2011
DOI: 10.1007/s10534-011-9498-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron-induced remodeling in cultured rat pulmonary artery endothelial cells

Abstract: Although iron is known to be a component of the pathogenesis and/or maintenance of acute lung injury (ALI) in experimental animals and human subjects, the majority of these studies have focused on disturbances in iron homeostasis in the airways resulting from exposure to noxious gases and particles. Considerably less is known about the effect of increased plasma levels of redox-reactive non-transferrin bound iron (NTBI) and its impact on pulmonary endothelium. Plasma levels of NTBI can increase under various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…In agreement with our study, it has been reported in rat pulmonary artery endothelial cells that F-actin polymerization and cellular remodeling can be induced by iron supplementation (Gorbunov et al, 2012). Furthermore, iron-induced rearrangements of the cytoskeleton can be partially eliminated in the presence of the iron chelator, N,N9-bis-(2-hydroxybenzyl)-ethylenediamine-N,N9-diacetic acid (Gorbunov et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our study, it has been reported in rat pulmonary artery endothelial cells that F-actin polymerization and cellular remodeling can be induced by iron supplementation (Gorbunov et al, 2012). Furthermore, iron-induced rearrangements of the cytoskeleton can be partially eliminated in the presence of the iron chelator, N,N9-bis-(2-hydroxybenzyl)-ethylenediamine-N,N9-diacetic acid (Gorbunov et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, iron-induced rearrangements of the cytoskeleton can be partially eliminated in the presence of the iron chelator, N,N9-bis-(2-hydroxybenzyl)-ethylenediamine-N,N9-diacetic acid (Gorbunov et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PhenGreen diacetate (PGD) is a hydrophobic, cell permeable molecule, which inside the cells is cleaved by cellular esterases into fluorescent PhenGreen (PG), and this hydrophilic product is accumulated inside the cells. Interaction of PG with various metal ions results in the quenching of PG fluorescence, thus allows the quantitative estimation of cellular metal concentrations [ 20 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The green fluorescence of PG is variably quenched in the presence of divalent metal ions, especially by heavy metal ions [ 19 ]. Therefore, this PGD loading and PG fluorescence measurement technology has been applied for the determination of iron or cadmium ions in various cellular systems [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, use of plumbagin, an iron chelator, ( Padhye et al, 2012 ) was found to limit proliferation in human PASMCs and decrease distal pulmonary artery remodeling in a rat model of PAH ( Courboulin et al, 2012 ). Additionally, iron was found to induce remodeling in cultured rat PAECs ( Gorbunov et al, 2012 ). Together, these studies indicate a role for iron availability in proliferation and remodeling.…”
Section: In Vitro and In Vivo Models Of Dmentioning
confidence: 99%